PERANCANGAN VISUAL IDENTITY JERUK SIAM GUNUANG OMEH KELOMPOK TANI FAJAR HARAPAN - RAHMAITI ARNIA SUKMA, Dr. Syafwndi, M.Sn., Drs. Ariusmedi. M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this article is to design the Visual Identity of Gunuang Omega, Siamese oranges, in   order to provide a visual identity and identity for Siamese oranges from the Fajar Harapan farmer  group, which will function later as (1) Designing a logo to display identity, from "Gunuang Omeh"  Siamese oranges, so that consumers can distinguish "Gunuang Omeh" Siamese oranges from their  competitors. (2) Inform the public in the form of logos that oranges do not, limes mudiak, oranges  and various other nicknames are jesigo. (3 ) Designing a logo that attracts consumers / target  audiences to know and buy jesigo products. (4) As a promotional media and to create a visual  identity in the form of a logo from jesigo and can be applied to various supporting media such as,  Posters, Web Banners, Stickers, Totebag , TShirt, Stationary Set and so on. The design stage starts  from data collection, data analysis and design. The process of collecting data through  observation, interviews and documentation, while the process of analyzing data with analysis of  5W1H.Keywords : Jesigo, Jeruk Siam Gunuang Omeh, Visual Identity.